The evolution of internal audit research: a bibliometric analysis of published documents (1926–2016). (2nd January 2019) - Behrend, Joel; Eulerich, Marc
ABSTRACT: Addressing the rise of internal auditing in the post-SOX era, this study examines the scientific transformation of the topic within current accounting research. In an attempt to shed light on the existing research themes and core works that have been shaping this topic, we combine co-citation and social network analysis to analyse citation patterns of 170 research articles published in five leading accounting journals between 1926 and 2016. The scientific landscape of internal auditing within accounting research is found to be highly fragmented and partly defined by internal auditors' relationships to other parties of the corporate governance framework. Additionally, results reveal the existence of a research nucleus which emphasises the increasingly important construct of internal audit quality.